Effects of Beverages with Variable Nutrients on Rehydration and Cognitive Function - Wong, S. H. S.; Sun, F.-H.; Huang, W. Y. J.; Chen, Y.-J. (International Journal of Sports Medicine, 2014)
The purpose of the present study was to investigate the effect of carbohydrate-electrolyte solution (CE), lemon tea (LT), and distilled water (DW) on rehydration and cognitive performance after 60 min of moderate exercise. 9 healthy males and 10 eumenorrheic females completed 3 runs in a randomized crossover study design. During the 4-h recovery (REC) period, they consumed either a volume of CE, LT or DW equal to 150% of their body mass (BM) loss during the previous run. The 3 beverages vary in carbohydrate and electrolyte content. A battery of cognitive tests was performed upon arrival, immediately after exercise, and at the end of REC. After the REC, the restoration of BM loss was lower in the DW and LT trials than that in the CE trial in the female participants (CE vs. LT vs. DW: 59.3±2.8 vs. 41.7±5.7 vs. 45.6±2.2%). When compared with the DW, the accuracy of performances during a working memory task in both males and females was higher in the CE and LT trials. The results suggested that during a short-term recovery, both LT and CE show certain beneficial effect in maintaining cognitive performance. However, CE appears to be more effective than LT and DW in rehydrating female participants.
Keywords: dehydration; recovery; carbohydrate-electrolyte solution; sex; moderate intensity exercise